Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1983
DOI: 10.1115/83-gt-142
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics of Hydrogen - Carbon Monoxide Based Gaseous Fuels

Abstract: An experimental rig program has been conducted with the objective of evaluating the combustion performance of a family of fuel gases based on a mixture of hydrogen and carbon monoxide. These gases, in addition to being members of a family, were also representative of those secondary fuels that could be produced from coal by various gasification schemes. In particular, simulated Winkler, Lurgi, and Blue-water low and medium energy content gases were used as fuels in the experimental combustor rig. The combustor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Dixon- Lewis and Williams (1969), expounded on the oxidation characteristics of hydrogen and carbon monoxide in 1969. The body of research into the basic combustion characteristics of gasified fuel includes studies on the flammability limits of mixed gas, consisting of CH 4 or H 2 diluted with N 2 , Ar or He (Ishizuka & Tsuji, 1980); a review of the flammability and explosion limits of H 2 and H 2 /CO fuels (Cohen, 1992); the impact of N 2 on burning velocity (Morgan & Kane, 1952); the effect of N 2 and CO 2 on flammability limits (Coward & Jones, 1952;Ishibasi et al, 1978); and the combustion characteristics of low calorific fuel (Folsom, 1980;Drake, 1984); studies by Merryman et al (1997), on NOx formation in CO flame; studies by Miller et al (1984), on the conversion characteristics of HCN in H 2 -O 2 -HCN-Ar flames; studies by Song et al (1980), on the effects of fuel-rich combustion on the conversion of the fixed nitrogen to N 2 ; studies by White et al (1983), on a rich-lean combustor for lowBtu and medium-Btu gaseous fuels; and research of the CRIEPI into fuel-NOx emission characteristics of low-calorific fuel, including NH 3 through experiments using a small diffusion burner and analyses based on reaction kinetics (Hasegawa et al, 2001). It is widely accepted that two-stage combustion, as typified by rich-lean combustion, is effective in reducing fuel-NOx emissions (Martin & Dederick, 1976;Yamagishi et al, 1974).…”
Section: Progress In Gas Turbine Combustion Technologies For Igccsmentioning
confidence: 99%
“…Dixon- Lewis and Williams (1969), expounded on the oxidation characteristics of hydrogen and carbon monoxide in 1969. The body of research into the basic combustion characteristics of gasified fuel includes studies on the flammability limits of mixed gas, consisting of CH 4 or H 2 diluted with N 2 , Ar or He (Ishizuka & Tsuji, 1980); a review of the flammability and explosion limits of H 2 and H 2 /CO fuels (Cohen, 1992); the impact of N 2 on burning velocity (Morgan & Kane, 1952); the effect of N 2 and CO 2 on flammability limits (Coward & Jones, 1952;Ishibasi et al, 1978); and the combustion characteristics of low calorific fuel (Folsom, 1980;Drake, 1984); studies by Merryman et al (1997), on NOx formation in CO flame; studies by Miller et al (1984), on the conversion characteristics of HCN in H 2 -O 2 -HCN-Ar flames; studies by Song et al (1980), on the effects of fuel-rich combustion on the conversion of the fixed nitrogen to N 2 ; studies by White et al (1983), on a rich-lean combustor for lowBtu and medium-Btu gaseous fuels; and research of the CRIEPI into fuel-NOx emission characteristics of low-calorific fuel, including NH 3 through experiments using a small diffusion burner and analyses based on reaction kinetics (Hasegawa et al, 2001). It is widely accepted that two-stage combustion, as typified by rich-lean combustion, is effective in reducing fuel-NOx emissions (Martin & Dederick, 1976;Yamagishi et al, 1974).…”
Section: Progress In Gas Turbine Combustion Technologies For Igccsmentioning
confidence: 99%
“…The body of research into the basic combustion characteristics of gasified fuel includes studies on the flammability limits of mixed gas, consisting of CH 4 or H 2 diluted with N 2 , Ar or He [47]; a review of the flammability and explosion limits of H 2 and H 2 /CO fuels [48]; the impact of N 2 on burning velocity [49]; the effect of N 2 and CO 2 on flammability limits [50,51]; and the combustion characteristics of low calorific fuel [52,53]; studies by Merryman et al [54], on NOx formation in CO flame; studies by Miller et al [55], on the conversion characteristics of HCN in H 2 -O 2 -HCN-Ar flames; studies by Song et al [56], on the effects of fuel-rich combustion on the conversion of the fixed nitrogen to N 2 ; studies by White et al [57], on a rich-lean combustor for low-Btu and medium-Btu gaseous fuels; and research of the CRIEPI into fuel-NOx emission characteristics of low-calorific fuel, including NH 3 through experiments using a small diffusion burner and analyses based on reaction kinetics [58][59][60][61]. It is widely accepted that two-stage combustion, as typified by rich-lean combustion, is effective in reducing fuel-NOx emissions [62,63].…”
Section: Low-nox Combustion Technologymentioning
confidence: 99%
“…There have been a huge number of researches about the combustion characteristics of gasified fuels (Morgan and Kane, 1962), (Coward and Jones, 1971), (Yamagishi et al, 1974), (Martin and Dederick, 1977), (Ishibasi et al, 1978), (Folsom et al, 1980), (Ishizuka and Tsuji, 1981), (White et al, 1983), (Drake et al, 1984), (D bbeling et al, 1996), (Zanello and Tasselli, 1996) and combustors (Pillsbury et al, 1976), (Battista and Farrell, 1979), (Clark et al, 1982), (Beebe et al, 1982), (D bbeling et al, 1994), (Cook et al, 1994). Earlier studies by author et al (for example, 1998a, 1999, 2001, 2003, 2005, 2007b) have suggested advantages of the reducing combustion to reduce both fuel-NOx emissions and thermal-NOx emissions in gasified fueled combustion through experiments and analyses.…”
Section: Effects Of Reducing Combustionmentioning
confidence: 99%